Evaluating the Taxonomic Status of the Mexican Gray Wolf and the Red Wolf: Spanish-Language Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Scientists strive to develop clear rules for naming and grouping living organisms. But taxonomy, the scientific study of biological classification and evolution, is often highly debated. Members of a species, the fundamental unit of taxonomy and evolution, share a common evolutionary history and a common evolutionary path to the future. Yet, it can be difficult to determine whether the evolutionary history or future of a population is sufficiently distinct to designate it as a unique species. A species is not a fixed entity – the relationship among the members of the same species is only a snapshot of a moment in time. Different populations of the same species can be in different stages in the process of species formation or dissolution. In some cases hybridization and introgression can create enormous challenges in interpreting data on genetic distinctions between groups. Hybridization is far more common in the evolutionary history of many species than previously recognized. As a result, the precise taxonomic status of an organism may be highly debated. This is the current case with the Mexican gray wolf (Canis lupus baileyi) and the red wolf (Canis rufus), and this publication provides a spanish-language summary of the assessment of the taxonomic status for each.
Keywords: Biology and Life Sciences

Evaluating the Taxonomic Status of the Mexican Gray Wolf and the Red Wolf - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Scientists strive to develop clear rules for naming and grouping living organisms. But taxonomy, the scientific study of biological classification and evolution, is often highly debated. Members of a species, the fundamental unit of taxonomy and evolution, share a common evolutionary history and a common evolutionary path to the future. Yet, it can be difficult to determine whether the evolutionary history or future of a population is sufficiently distinct to designate it as a unique species.
Keywords: Biology and Life Sciences

A Research Strategy to Examine the Taxonomy of the Red Wolf - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
A Research Strategy to Examine the Taxonomy of the Red Wolf provides independent guidance about taxonomic research on the red wolf, Canis rufus. Building from the 2019 report Evaluating the Taxonomic Status of the Mexican Gray Wolf and the Red Wolf, this report reviews and ranks research applications to determine the taxonomy of wild canid populations in southern Louisiana and other relevant locations. The report then develops a research strategy to examine the evolutionary relationships between ancient red wolves, the extant managed red wolf populations, and the unidentified canid populations.
Keywords: Biology and Life Sciences

Variation and Evolution in Plants and Microorganisms: Toward a New Synthesis 50 Years After Stebbins - National Academy of Sciences (The National Academies Press, 2000)
"The present book is intended as a progress report on [the] synthetic approach to evolution as it applies to the plant kingdom." With this simple statement, G. Ledyard Stebbins formulated the objectives of Variation and Evolution in Plants, published in 1950, setting forth for plants what became known as the "synthetic theory of evolution" or "the modern synthesis." The pervading conceit of the book was the molding of Darwin's evolution by natural selection within the framework of rapidly advancing genetic knowledge. At the time, Variation and Evolution in Plants significantly extended the scope of the science of plants. Plants, with their unique genetic, physiological, and evolutionary features, had all but been left completely out of the synthesis until that point. Fifty years later, the National Academy of Sciences convened a colloquium to update the advances made by Stebbins. This collection of 17 papers marks the 50th anniversary of the publication of Stebbins' classic. Organized into five sections, the book covers: early evolution and the origin of cells, virus and bacterial models, protoctist models, population variation, and trends and patterns in plant evolution.
Keywords: Biology and Life Sciences

(NAS Colloquium) Variation and Evolution in Plants and Microorganisms: Towards a New Synthesis: 50 Years after Stebbins (The National Academies Press, 2000)
In 1991, the National Academy of Sciences inaugurated a series of scientific colloquia, five or six of which are scheduled each year under the guidance of the NAS Council's Committee on Scientific Programs. Each colloquium addresses a scientific topic of broad and topical interest, cutting across two or more of the traditional disciplines. Typically two days long, colloquia are international in scope and bring together leading scientists in the field. Papers from colloquia are published in the Proceedings of the National Academy of Sciences (PNAS). The colloquium "Variation and Evolution in Plants and Microorganisms: Toward a New Synthesis 50 Years After Stebbins" celebrates the 50th anniversary of the publication of Stebbins' classic book, Variation and Evolution in Plants. Variation and Evolution in Plants, published in 1950, the last of a quartet of classics that, in the second quarter of the 20th century, set forth what became known as the "synthetic theory of evolution" or "the modern synthesis." The other books are Theodosius Dobzhansky's Genetics and the Origin of Species (2), Ernst Mayr's Systematics and the Origin of Species (3), and George Gaylord Simpson's Tempo and Mode in Evolution (4). The pervading theory of these books is the molding of Darwin's evolution by natural selection within the framework of rapidly advancing genetic knowledge. Variation and Evolution in Plants distinctively extends the scope of the other books to the world of plants. Dobzhansky's perspective was that of the geneticist. Mayr's was that of the zoologist and systematist. Simpson's was that of the paleobiologist. All four books were outcomes of the famed Jesup Lectures at Columbia University. Plants, with their unique genetic, physiological, and evolutionary features, had been left out of the synthesis until then. In 1941, the eminent botanist Edgar Anderson was invited to write botany's analogue to Mayr's Systematics and the Origin of the Species and to publish it jointly with Mayr's book. Anderson did not fulfill the task, and Stebbins was thereafter invited to deliver the Jesup Lectures in 1947. Variation and Evolution in Plants is the outgrowth of those Lectures.
Keywords: Biology and Life Sciences

Field Testing Genetically Modified Organisms: Framework for Decisions - National Research Council (The National Academies Press, 1989)
Potential benefits from the use of genetically modified organisms—such as bacteria that biodegrade environmental pollutants—are enormous. To minimize the risks of releasing such organisms into the environment, regulators are working to develop rational safeguards. This volume provides a comprehensive examination of the issues surrounding testing these organisms in the laboratory or the field and a practical framework for making decisions about organism release. Beginning with a discussion of classical versus molecular techniques for genetic alteration, the volume is divided into major sections for plants and microorganisms and covers the characteristics of altered organisms, past experience with releases, and such specific issues as whether plant introductions could promote weediness. The executive summary presents major conclusions and outlines the recommended decision-making framework.
Keywords: Biology and Life Sciences

Immunodeficient Rodents: A Guide to Their Immunobiology, Husbandry, and Use - National Research Council (The National Academies Press, 1989)
This volume is an indispensable reference on the nature of immune defects in rodents and the special techniques necessary to maintain and breed them. The authors describe 64 inbred, hybrid, and mutant strains of rodents, each with some immune defect; explain mechanisms for ensuring genetic purity; and provide a standardized nomenclature for different varieties. Subsequent sections summarize and provide references on the genetics, pathophysiology, husbandry, and reproduction of each of the various strains as well as sound advice on planning for the selection, transportation, housing, and maintenance of these animals.
Keywords: Biology and Life Sciences

Genetically Engineered Crops: Experiences and Prospects - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Genetically engineered (GE) crops were first introduced commercially in the 1990s. After two decades of production, some groups and individuals remain critical of the technology based on their concerns about possible adverse effects on human health, the environment, and ethical considerations. At the same time, others are concerned that the technology is not reaching its potential to improve human health and the environment because of stringent regulations and reduced public funding to develop products offering more benefits to society. While the debate about these and other questions related to the genetic engineering techniques of the first 20 years goes on, emerging genetic-engineering technologies are adding new complexities to the conversation.
Keywords: Biology and Life Sciences; Agriculture

Mendel in the Kitchen: A Scientist's View of Genetically Modified Foods - Fedoroff, Nina V.; Brown, Nancy Marie (The National Academies Press, 2004)
While European restaurants race to footnote menus, reassuring concerned gourmands that no genetically modified ingredients were used in the preparation of their food, starving populations around the world eagerly await the next harvest of scientifically improved crops. Mendel in the Kitchen provides a clear and balanced picture of this tangled, tricky (and very timely) topic. Any farmer you talk to could tell you that we've been playing with the genetic makeup of our food for millennia, carefully coaxing nature to do our bidding. The practice officially dates back to Gregor Mendel—who was not a renowned scientist, but a 19th century Augustinian monk. Mendel spent many hours toiling in his garden, testing and cultivating more than 28,000 pea plants, selectively determining very specific characteristics of the peas that were produced, ultimately giving birth to the idea of heredity—and the now very common practice of artificially modifying our food. But as science takes the helm, steering common field practices into the laboratory, the world is now keenly aware of how adept we have become at tinkering with nature—which in turn has produced a variety of questions. Are genetically modified foods really safe? Will the foods ultimately make us sick, perhaps in ways we can't even imagine? Isn't it genuinely dangerous to change the nature of nature itself? Nina Fedoroff, a leading geneticist and recognized expert in biotechnology, answers these questions, and more. Addressing the fear and mistrust that is rapidly spreading, Federoff and her co-author, science writer Nancy Brown, weave a narrative rich in history, technology, and science to dispel myths and misunderstandings. In the end, Fedoroff arues, plant biotechnology can help us to become better stewards of the earth while permitting us to feed ourselves and generations of children to come. Indeed, this new approach to agriculture holds the promise of being the most environmentally conservative way to increase our food supply.
Keywords: Explore Science; Biology and Life Sciences

Crocodiles as a Resource for the Tropics - National Research Council (The National Academies Press, 1983)
Keywords: Biology and Life Sciences

Symposium on the Role of the Vestibular Organs in Space Exploration (The National Academies Press, 1970)
Keywords: Biology and Life Sciences

Biotechnology: An Industry Comes of Age - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 1986)
Keywords: Biology and Life Sciences

Recent Developments in Vision Research - National Research Council (The National Academies Press, 1966)
Keywords: Biology and Life Sciences

Techniques for the Study of Primate Population Ecology - National Research Council (The National Academies Press, 1981)
Keywords: Biology and Life Sciences

Neotropical Primates: Field Studies and Conservation : Proceedings of a Symposium on the Distribution and Abundance of Neotropical Primates - National Research Council (The National Academies Press, 1976)
Keywords: Biology and Life Sciences

Biology and the Exploration of Mars (The National Academies Press, 1966)
Until recent years the origin of life and its possible occurrence elsewhere in the universe have been matters for speculation only. The rapid growth of molecular biology since 1940 has, to be sure, made it possible to discuss life's origins in far more precise and explicit terms than was possible earlier; and the subject entered a new experimental phase in the 1950's with successful abiogenic synthesis of important biochemical substances in conditions simulating the presumptive environment of the primitive Earth. But the real transformation that the subject has undergone stems from the spectacular growth of space technology in the last decade. The possibility of life's origin and occurrence on planets other than ours is no longer limited to idle speculation: it has entered the realm of the testable, of science in the strict sense. Given the rockets now available, and especially those available by 1969, it has become fully realistic to consider plans for the biological exploration of Mars. Biology and the Exploration of Mars: Report of a Study concludes that the exploration of Mars—motivated by biological questions—does indeed merit the highest scientific priority in the nation's space program over the next decades. This report further concludes that the favorable opportunities for exploration between 1969 and 1973 can and should be exploited as vigorously as possible. The report considers the potential scientific yields of exploration, the possibility of life occurring on Mars and our ability to detect it with available and foreseeable technology, and gains from further astronomical work from Earth, by Martian fly-by missions, Martian orbiters, and Martian landers. Biology and the Exploration of Mars: Report of a Study contains the findings of the study, a postscript discussing the significance of the observations obtained during the flight of Mariner IV past Mars, and a collection of the working papers that formed the basis of discussions.
Keywords: Space and Aeronautics; Biology and Life Sciences

Organic Matter and the Moon, by Carl Sagan - National Research Council (The National Academies Press, 1961)
The immediate future seems to hold both the promise and the responsibility of extensive contact between man-made objects and the Moon. Current United States plans tentatively call for the soft landing on the Moon of instrumentation designed to detect indigenous organisms or organic matter, possibly in a roving vehicle, by 1964-67 in the Surveyor and Prospector Programs. The Soviet Union apparently has the capability of performing similar experiments at an earlier date. It is clear that positive results would give significant information on such problems as the early history of the Solar System, the chemical composition of matter in the remote past, the origin of life on Earth, and the distribution of life beyond the Earth. By the same token, biological contamination of the Moon would represent an unparalleled scientific disaster, eliminating possible approaches to these problems. Because of the Moon's unique situation as a large unweathered body at an intermediate distance from the Sun, scientific opportunities lost on the Moon may not be recoupable elsewhere. This monograph is concerned with the possibility of finding indigenous lunar organisms or organic matter, and with the possibility of their contamination by deposited terrestrial organisms or organic matter.
Keywords: Space and Aeronautics; Biology and Life Sciences

Safety of Genetically Engineered Foods: Approaches to Assessing Unintended Health Effects - Institute of Medicine; National Research Council (The National Academies Press, 2004)
Assists policymakers in evaluating the appropriate scientific methods for detecting unintended changes in food and assessing the potential for adverse health effects from genetically modified products. In this book, the committee recommended that greater scrutiny should be given to foods containing new compounds or unusual amounts of naturally occurring substances, regardless of the method used to create them.
Keywords: Biology and Life Sciences

Systematics and the Origin of Species: On Ernst Mayr's 100th Anniversary - National Academy of Sciences (The National Academies Press, 2005)
In December 2004, the National Academy of Sciences sponsored a colloquium on "Systematics and the Origin of Species" to celebrate Ernst Mayr's 100th anniversary and to explore current knowledge concerning the origin of species. In 1942, Ernst Mayr, one of the twentieth century's greatest scientists, published Systematics and the Origin of Species, a seminal book of the modern theory of evolution, where he advanced the significance of population variation in the understanding of evolutionary process and the origin of new species. Mayr formulated the transition from Linnaeus's static species concept to the dynamic species concept of the modern theory of evolution and emphasized the species as a community of populations, the role of reproductive isolation, and the ecological interactions between species.
Keywords: Biology and Life Sciences

The Genomic Revolution: Implications for Treatment and Control of Infectious Disease: Working Group Summaries (The National Academies Press, 2006)
The 2005 conference, "The Genomic Revolution: Implications for Treatment and Control of Infectious Disease," attracted scientists, engineers, and medical researchers to work on new interdisciplinary responses using genomics to treat and control infectious diseases. Eleven conference working groups gave the participants eight hours to develop new research approaches to problems in infectious disease using genomics. Among the challenges were designing a new device to detect viral and bacterial pathogens; how best to use $100 million to prevent a future pandemic flu outbreak; how to improve rapid response to an outbreak of disease and reduce the cost of diagnostic tests; and how to sequence an individual's genome for under $1,000. Representatives from public and private funding organizations, government, industry, and the science media also participated in the working groups. This book provides a summary of the conference working groups. For more information about the conference, visit www.keckfutures.org/genomics. The National Academies Keck Futures Initiative was launched in 2003 to stimulate new modes of scientific inquiry and break down the conceptual and institutional barriers to interdisciplinary research. The National Academies and the W.M. Keck Foundation believe considerable scientific progress and social benefit will be achieved by providing a counterbalance to the tendency to isolate research within academic fields. The Futures Initiative is designed to enable researchers from different disciplines to focus on new questions upon which they can base entirely new research, and to encourage better communication between scientists as well as between the scientific community and the public. Funded by a $40 million grant from the W.M. Keck Foundation, the National Academies Keck Futures Initiative is a 15-year effort to catalyze interdisciplinary inquiry and to enhance communication among researchers, funding agencies, universities, and the general public with the object of stimulating interdisciplinary research at the most exciting frontiers. The Futures Initiative builds on three pillars of vital and sustained research: interdisciplinary encounters that counterbalance specialization and isolation; the identification and exploration of new research topics; and communication that bridges languages, cultures, habits of thought, and institutions. Toward these goals, the National Academies Keck Futures Initiative incorporates three core activities each year: Futures conferences, Futures grants, and National Academies Communication Awards.
Keywords: Biology and Life Sciences